Editing the 2004 AMJ Best Article Award Winner - Bergh, Donald D. (Academy of Management Journal, 2006)
The author discusses his experience serving as the action editor for a three-person panel that reviewed an academic paper submitted for publication. Opinions varied among the reviewers as to the paper's merit, and after a revised manuscript was submitted one of the editors thought the paper had deteriorated in quality. This same reviewer still had reservations after a third edition arrived, but the author decided they were not strong enough to prevent him from conditionally accepting the manuscript for publication. The experience convinced him that papers benefit considerably from peer review, and from authors' willingness to honestly address reviewers' concerns.